Overfishing Increases the Carbon Footprint of Seafood Production From Small-Scale Fisheries - Ferrer, Erica M.; Giron-Nava, Alfredo; Aburto-Oropeza, Octavio (Frontiers in Marine Science, 2022)
Small-scale fisheries (SSFs) and the foods they produce are extremely important, contributing 25–50% of global seafood landed for direct consumption. In some cases, SSFs provide seafoods with an exceptionally low carbon footprint, but like all food, it is important to understand the factors that regulate that footprint in the face of increasing demand and a worsening climate-ecological crisis. We utilize long-term fisheries monitoring data from Northwest Mexico to generate novel stock assessments and, subsequently, test the relationship between underlying fishery biomass and fuel intensity observed among several motorized SSFs. Using fuel data from over 4,000 individual fishing trips, in combination with estimated biomass data for 19 regional stocks, we show that the fuel footprint per kilogram of seafood increases sharply as the stock’s underlying annual biomass (B) falls below its estimated biomass at Maximum Sustainable Yield (BMSY). We find an inverse relationship between B/BMSY and fuel intensity using a test for simple correlation between the two (r= -0.44), a linear regression analysis (R2adj. = 0.17), and a mixed-effects model with gear type, year, and genus modelled as random effects. These results indicate that efforts to end overfishing, rebuild fishery stocks, and/or minimize intensive fishing practices will help to decrease the carbon emissions generated by motorized wild-catch fishing. We anticipate that this study will contribute an important “missing link” to discussions on how best to secure climate-resilient fisheries and, ideally, help SSF stakeholders garner recognition and support for SSFs in this context.